A função socioambiental da terra: uma análise das decisões liminares proferidas nos autos de ações possessórias em trâmite no Estado da Paraíba - Rocha, Olímpio de Moraes (2018)
This dissertation has as its theme the study of the socioenvironmental constitutional function of land in judicial decisions that appraise preliminary injunctions in possession injunctions arising from agrarian conflicts filed from 2015 to 2017 against the Landless Rural Workers Movement in the State of Paraíba. This work is contained in the research line "Theories of Decision and Socioenvironmental Sustainability", of the Concentration Area in Economic Law, of the Graduate Program in Legal Sciences in Federal University of Paraíba. The research problem touches on the interpretation to be given to Chapter III of Title III and, especially, to Article 561 of the New Civil Procedure Code, which, like the old Civil Procedure Code, still lodges the possession of land in litigation collective agrarians without conditioning said lair to the fulfillment of the socio-environmental function of the land, raising doubts as to whether this would be in accordance with the constitutional legal order, here seen under the hermeneutic-concretizing method and under the so-called Open Society Theory of Interpreters of the Constitution, of the work of the German jurist Peter Häberle, the theoretical framework on which this work is based. The main objective is to illustrate how and if the Judiciary of Paraíba requires the fulfillment of the socioenvironmental function of the land for the granting of a preliminary injunction in possessory actions in agrarian conflicts and what is the judicial position adopted before the constitutional provisions related to the subject. The research was done by literature review and case studies based on the possessory actions filed in the last three years against MST in Paraíba, referring to the cases described in the third chapter. The evidenced results mostly show negative responses to the problem, that is, the legal protection of the rural property in Paraiba was not conditioned to the fulfillment of the socio-environmental constitutional function of the land in the preliminary decisions proclaimed in almost all the surveyed processes. Therefore, it is concluded that the Judiciary's action in Paraíba does not contribute to the implementation of the Federal Constitution, since it does not protect the claims of the population in a situation of vulnerability without access to land, contributing to the outbreak of agrarian conflicts, which ends up going against the open, plural and democratic society advocated by Peter Häberle.